2010
DOI: 10.3171/2009.7.jns09239
|View full text |Cite
|
Sign up to set email alerts
|

Language dominance and mapping based on neuromagnetic oscillatory changes: comparison with invasive procedures

Abstract: This study is the first in which magnetoencephalography (MEG) was used to determine language dominance in a large population, and the results were compared with those of the Wada test. Moreover, language localization results obtained using MEG were compared with those obtained by invasive mapping. The authors' method, which is based on neuromagnetic oscillatory changes, is a new approach for noninvasively evaluating the frontal language areas, a procedure that has been problematic using MEG dipole methods. Syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
65
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 43 publications
10
65
0
Order By: Relevance
“…We demonstrated distinct characteristics of frequency profiles and the time course of language-related oscillatory changes. ERDs in the alpha, beta and low gamma bands and the power increase in the theta band were localized in the word-reading related areas as we previously reported (Hirata et al, 2010;Hirata et al, 2004;Hirata et al, 2007). Spatial distributions of ERDs were different depending on the frequency bands.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…We demonstrated distinct characteristics of frequency profiles and the time course of language-related oscillatory changes. ERDs in the alpha, beta and low gamma bands and the power increase in the theta band were localized in the word-reading related areas as we previously reported (Hirata et al, 2010;Hirata et al, 2004;Hirata et al, 2007). Spatial distributions of ERDs were different depending on the frequency bands.…”
Section: Discussionmentioning
confidence: 51%
“…Thus, the spatiotemporal distributions of ERD and ERS can be obtained precisely using SAM. We used this technique to investigate language processing based on cerebral oscillatory changes and have previously reported that cerebral oscillatory changes during silent reading are localized in language-related areas (Hirata et al, 2010;Hirata et al, 2004;Hirata et al, 2007;Ihara et al, 2003a). We found that the frontal language areas are consistently desynchronized in the beta and low gamma bands during silent reading (Hirata et al, 2010(Hirata et al, , 2004.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…In a study using electrocorticography, Sinai et al 88 found reasonable agreement between areas with language-related changes in the gamma band and positive sites found with ESM. Recently, Hirata et al 32 used MEG and event-related desynchronization to map language areas for use in neurosurgery. Although these are still experimental studies, it seems a promising new way to look at localized brain function.…”
Section: New Concepts Of Functional Topographymentioning
confidence: 99%
“…This technique has been demonstrated to be effective in localizing source activation associated with various cognitive tasks including speech, motor and sensory processing in [29][30][31]. It has been used effectively in various clinical settings including preoperative localization of motor cortex for tumor resection, identification of epileptogenic foci and mapping language areas as demonstrated in [32][33][34][35].…”
Section: Synthetic Aperture Magnetometry (Sam) and Source Space Bcimentioning
confidence: 99%